2007
DOI: 10.1007/s10120-006-0410-7
|View full text |Cite
|
Sign up to set email alerts
|

Expression of phosphorylated Akt (pAkt) in gastric carcinoma predicts prognosis and efficacy of chemotherapy

Abstract: Background. The Akt signaling pathway controls the survival and growth of human cancers. We investigated the expression of phosphorylated Akt (pAkt) in patients with gastric cancer. Methods. The expression of pAkt was immunohistochemically examined in 140 gastric cancer patients who underwent a gastrectomy. The expression of pAkt was evaluated based on staining intensity, and staining was classifi ed as negative or positive. We examined the expression of pAkt and its association with the clinicopathological fi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

2
30
0
1

Year Published

2007
2007
2020
2020

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 50 publications
(33 citation statements)
references
References 25 publications
2
30
0
1
Order By: Relevance
“…Diverse opinions also exist regarding prognosis in relation to pAkt expressions. A large majority of studies have asserted that pAkt expression is correlated with poor prognosis in NSCLC [11,17,26], breast cancer [27], gastric cancer [20], and renal cell carcinoma [15]. However, Chan et al [28] have reported that pAkt expression is not significantly related to patient survival, but is inversely related to tumor grade and size in breast cancer.…”
Section: Discussionmentioning
confidence: 98%
See 1 more Smart Citation
“…Diverse opinions also exist regarding prognosis in relation to pAkt expressions. A large majority of studies have asserted that pAkt expression is correlated with poor prognosis in NSCLC [11,17,26], breast cancer [27], gastric cancer [20], and renal cell carcinoma [15]. However, Chan et al [28] have reported that pAkt expression is not significantly related to patient survival, but is inversely related to tumor grade and size in breast cancer.…”
Section: Discussionmentioning
confidence: 98%
“…Once activated, signaling through Akt can be propagated to a diverse array of substrates, including mTOR, a key regulator of protein translation [9]. Moreover, activation of the Akt/mTOR pathway confers resistance to many types of cancer therapy [10][11][12][13][14] and is a poor prognostic factor for many cancers [15][16][17][18][19][20]. However, the prognostic significance and predictive value for response to therapy targeting activated Akt (phosphorylated Akt) or mTOR is not clearly established in the lung cancer patients.…”
mentioning
confidence: 99%
“…Many previous studies from various countries have examined clinicopathologic prognostic factors for GC after radical gastrectomy. Researchers have regarded controversial factors, including sex, age at diagnosis, tumor diameter, gastric wall invasion, surgical margins, differentiation, lymph node metastasis, and TNM stage as independent prognostic factors in different reports (Murakami et al 2007;Shiraishi et al 2000;Yokota et al 2004;Zheng et al 2004). However, they did not reach a consensus concerning which clinicopathologic factors were associated with the optimum prognosis (Potrc et al 2007;Yokota et al 2002).…”
Section: Discussionmentioning
confidence: 99%
“…Among numerous proangiogenic factor, vascular endothelial growth factor (VEGF) has been established as the major angiogenic factor (17). Frequently observed in gastric cancer (18 -20), overexpression of VEGF closely correlates with lymph node metastasis (21), liver metastasis (22), age (23), and tumor size (24) and often indicates a poor prognosis (25,26) and therapy resistance (27). Although VEGF is constitutively expressed in many tumor cells, its expression is subject to several regulatory mechanisms (17).…”
mentioning
confidence: 99%